Behavior navigation system for harsh environments. (1st February 2016) - Oyama, Eimei; Shiroma, Naoji; Watanabe, Norifumi; Agah, Arvin; Omori, Takashi; Suzuki, Natsuo
Abstract: Performing general human behavior by experts' navigation is expected to be realized as wearable technologies and computing systems are further developed. We have proposed and developed the prototype of the advanced behavior navigation system (BNS) using augmented reality technology. Utilizing the BNS, an expert can guide a non-expert to perform a variety of tasks. The BNSs are useful in tasks to be performed in harsh and hazardous environments, such as factories, construction sites, and areas affected by natural disasters (e.g. earthquakes and tsunamis). In this paper, we present a BNS that is specifically designed to operate in harsh environments, with characteristics such as wet or dusty conditions. The implementation, experimental results, and evaluation of the BNS prototypes are presented. Abstract :